The kingmaker's daughter - Gregory, Philippa (New York : Simon & Schuster, 2012)
"Kingmaker" Richard, Earl of Warwick, uses his daughters as political pawns before their strategic marriages place them on opposing sides in a royal war that will cost them everyone they love.
"A Touchstone Book"
Includes bibliographical references (p. 413-417).
Keywords: Anne, -- Queen, consort of Richard III, King of England, -- 1456-1485 -- Fiction; Sisters -- England -- Fiction; Great Britain -- History -- Edward IV, 1461-1483 -- Fiction; Biographical fiction; Historical fiction